Mengembangkan Produk pada Layanan Jasa Informasi Perbankan dengan Shariah Governance untuk Pengaplikasian Keuangan Digital Syariah - Hasibuan, Muthia Hafsari; Padli Nasution, M. Irwan (Sci-tech Journal, 2023)
With the growing development of Islamic banking in Indonesia, there is an increasing need for a development of products and services in Islamic banks. This is done with the aim of meeting market needs by increasing competitiveness in the scope of Islamic banking in the era of the industrial revolution 4.0. Hence the need for a implementation of GCG. By applying GCG principles which have an important role in achieving business continuity (sustainability), namely Islamic banks that still pay attention to common interests. The implementation itself is a manifestation of the responsibility of Islamic banks to the public that Islamic banks must be operated properly, expertly and prudently (prudent). With the development of the times and the advancement of technology, there is an increasing need for an Islamic financial technology in the use of technology-based financial services that are more efficient. Keywords: sharia bank products and services, sharia governance, sharia digital finance